2000
DOI: 10.1128/jcm.38.10.3825-3826.2000
|View full text |Cite
|
Sign up to set email alerts
|

InTray GC Medium Versus Modified Thayer-Martin Agar Plates for Diagnosis of Gonorrhea from Endocervical Specimens

Abstract: A new self-contained medium system for the cultivation ofNeisseria gonorrhoeae was compared to modified Thayer-Martin medium for the diagnosis of gonorrhea from endocervical specimens. There was no difference in the ability of the two methods to support the growth of N. gonorrhoeae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…This study clearly demonstrates that a nutritive system such as the InTray GC would be optimal to transport viable N. gonorrhoeae to the laboratory. These results support a previous study that demonstrated equivalent recovery of N. gonorrhoeae from InTray GC and MTM plates inoculated with endocervical specimens from women presenting at a sexually transmitted disease clinic (Beverly et al, 2000). Acceptability of a non-nutritive transport system was limited to Amies medium inoculated with either the Copan Eswab or BD CultureSwab MaxV.…”
supporting
confidence: 91%
“…This study clearly demonstrates that a nutritive system such as the InTray GC would be optimal to transport viable N. gonorrhoeae to the laboratory. These results support a previous study that demonstrated equivalent recovery of N. gonorrhoeae from InTray GC and MTM plates inoculated with endocervical specimens from women presenting at a sexually transmitted disease clinic (Beverly et al, 2000). Acceptability of a non-nutritive transport system was limited to Amies medium inoculated with either the Copan Eswab or BD CultureSwab MaxV.…”
supporting
confidence: 91%
“…Further, N. gonorrhoeae isolates were confirmed by Real Time PCR assay. For preservation, gonococcal strains were subcultured onto plain MTM agar plates, incubated in similar conditions [38], harvested after a 24 h. incubation and preserved in duplicates in skimmed milk with 10% glycerol. The duplicates were stored at −20 • C freezer until the time for analysis.…”
Section: Clinical Isolatesmentioning
confidence: 99%
“…The overall prevalence of PPNG was 73.7% (95% CI: 65.7, 80.8%), with 56.7% and 43.3% observed in women and men, respectively. The overall prevalence of QRNG was 87.8% and those having high-level resistance [HLR], low-level resistance [LLR] and susceptible (NQR) were 52.4% (86), 23.2% (38), 24.4% (40), respectively. Prevalence of TRNG, non-TRNG and tetracycline-susceptible were 89.3% (125), 9.3% (13) and 1.4% (2), respectively.…”
Section: Prevalence Of Antimicrobial and Multi-drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have examined the difference in viability between different commercially available transport systems and generally found that the InTray GC1, a CO 2 generating packaging medium manufactured by BioMed Diagnostics, had a high rate of recovery after extended transport times [7]. Additionally, InTray GC plates have a shelf life of approximately one year, so are well-suited for use in settings where standard chocolate agar plates may not be widely available or viable after storage [8]. In an effort to build upon these previous studies, we assessed bacterial recovery of clinical isolates of N. gonorrhoeae in transport conditions in the InTray GC 72 hours after an initial period of incubation.…”
Section: Introductionmentioning
confidence: 99%